(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Antimullerian hormone (AMH) is a promising marker for polycystic ovarian morphology (PCOM). Objective: To determine the usefulness of combining the AMH-PCOM criterion with ovarian volume by ultrasonography (USG-PCOM) criterion in the diagnosis and phenotype distribution in patients with polycystic ovary syndrome (PCOS). Methods: This cross-sectional observational study included 160 newly detected PCOS patients on the basis of modified Rotterdam criteria with the same definitions of hyperandrogenism and oligo/anovulation. For PCOM, a combined-PCOM criterion by the presence of either USG-PCOM (OV >10 mL) and/or AMH-PCOM (AMH ≥3.5 ng/mL) criteria was taken. AMH was analyzed by an enzyme-linked immunosorbent assay. Clinical and biochemical features and luteinizing hormone/follicle-stimulating hormone ratio (LFR) were assessed. The association of combined-PCOM criterion with these features and phenotypes of PCOS were analyzed. Results: USG-PCOM outperformed AMH-PCOM by missing less PCOM (0.6% vs. 5.6%). When they were combined (USG-PCOM and/or AMH-PCOM), phenotype B almost disappeared (5.0%). After removing phenotype B, there was no discordance between the criteria as well as similar metabolic features and LFR among the rest of the phenotypes (NS for all). Conclusions: Complementing the USG-PCOM criterion, the AMH-PCOM criterion almost removed phenotype B and made the other phenotypes similar with respect to metabolic features and LFR in patients with PCOS. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023;2(1): 8-13